AGW 618 - Marketing Management - August - September 1998 - PPP, Pusat Pengajian Pengurusan (1998)
UNIVERSITI SAINS MALAYSIA Master of Business Administration First Semester Examination Academic Session 1998/1999 August/September 1998 AGW 618 - Marketing Management Time: [3 Hours]